Было 12 разбойников: роман / Павел Куляшов - Куляшов Павел Федорович (Удмуртия, 1994)
Экземпляры: ф.10 (2000) / Инвентарный номер: 41953 / Цена: / Сис.шифр: 84(2Рос.Удм)6-4 / Авт.знак: К 90 / ГРНТИ: 17.82.31 / ББК: 84(2Рос.Удм)6-44